First-line treatment of metastatic castration-resistant prostate cancer: the real-world Italian cohort of the Prostate Cancer Registry. Issue 2 (April 2023) - Galli, Luca; Chiuri, Vincenzo Emanuele; Di Lorenzo, Giuseppe; Pisconti, Salvatore; Rossetti, Sabrina; Sirotova, Zuzana; Muto, Andrea; Petrioli, Roberto; De Tursi, Michele; Sbrana, Andrea; Francolini, Giulio; Ardizzoia, Antonio; et al.
Background: With the availability of multiple treatment options for metastatic castration-resistant prostate cancer (mCRPC), new real-world data on disease management and drugs' performance are needed. Methods: We described characteristics, management and clinical outcomes of patients receiving first-line mCRPC treatment within the Italian cohort of the real-world, prospective, international Prostate Cancer Registry. Patients were enrolled consecutively (2013-2016) in 32 Italian sites and followed for 3 years. Results: 238 patients were included: 157 received first-line abiraterone acetate plus prednisone ("abiraterone" thereafter) and 70 first-line docetaxel; 11 patients receiving other treatments were not considered. Compared with docetaxel-treated patients, those receiving abiraterone were significantly older (age ⩾75: 63.7% vs 38.6%), less frequently had a Gleason score >8 (48.2% vs 67.6%, p<0.005) at initial diagnosis, and more frequently an ECOG score ⩾1 (52.7% vs 36.2%, p<0.05) and comorbidities (76.4% vs 57.1%, p<0.05) at baseline; they reported a lower analgesic use (15.3% vs 30%, p<0.005). In the abiraterone group (median follow-up 22.1 months), median time to progression (TTP) and progression-free survival (PFS) were, respectively, 14.4 months (95% confidence interval, CI, 10.6-18.0) and 13.0 months (95% CI, 9.1-16.8); median overall survival (OS) was not reached, and 3-year OS was 59.1%. In the docetaxel treatment group (median follow-up 25.3 months), median TTP, PFS and OS were, respectively, 8.2 months (95% CI, 6.1-10.3), 8.2 months (95% CI, 5.8-10.3) and 33.2 months (95% CI, 19.2-not estimable). Conclusion: This investigation provided valuable information on the overall mCRPC treatment pattern and the effectiveness of first-line abiraterone and docetaxel in a population representative of everyday practice.